High-dose therapy and autologous stem cell transplantation in patients with POEMS syndrome: a retrospective study of the Plasma Cell Disorder sub-committee of the Chronic Malignancy Working Party of the European Society for Blood & Marrow Transplantation - Cook, Gordon C.; Schönland, Stefan (Haematologica, 2017)
POEMS syndrome is a rare para-neoplastic syndrome secondary to a plasma cell dyscrasia. Effective treatment can control the disease-related symptom complex. We describe the clinical outcome of autologous stem cell transplantation for patients with POEMS syndrome, determining the impact of patient- and disease-specific factors on prognosis. One hundred and twenty-seven patients underwent an autologous stem cell transplantation between 1997-2010 with a median age of 50 years (range 26-69 years). Median time from diagnosis to autologous stem cell transplantation was 7.5 months with 32% of patients receiving an autologous stem cell transplantation more than 12 months from diagnosis. Engraftment was seen in 97% patients and engraftment syndrome was documented in 23% of autologous stem cell transplantation recipients. Hematologic response was characterized as complete response in 48.5%, partial response in 20.8%, less than partial repsonse in 30.7%. With a median follow up of 48 months (95%CI: 38.3, 58.6), 90% of patients are alive and 16.5% of patients have progressed. The 1-year non-relapse mortality was 3.3%. The 3-year probabilities of progression-free survival and overall survival are 84% and 94%, respectively, with 5-year probabilities of progression-free survival and overall survival of 74% and 89%. In a cohort of graft recipients, detailed organ-specific symptom response demonstrated clear symptom benefit after autologous stem cell transplantation especially in relation to neurological symptom control. The data analyzed in this study demonstrate the clinical utility of autologous stem cell transplantation for patients with POEMS syndrome.